Ultra short race pace training (USRPT) in swimming. Do the volume and interval matter? A scoping review - Papadimitriou, K. (Physiologia, 2024)
Background: Ultra-short race-pace training (USRPT) is designed to accustom swimmers to the pace of an event by using high volume and submaximal intensity with short intervals. However, due to imprecise data on volume and interval, further investigation is necessary. This scoping review aims to provide evidence-based insights into the advantages and disadvantages of recommended volumes and intervals during USRPT, guiding swimming coaches and offering practical advice regarding this training method.